Backbone modified TBA analogues endowed with antiproliferative activity - Esposito, Veronica; Russo, Annapina; Amato, Teresa; Varra, Michela; Vellecco, Valentina; Bucci, Mariarosaria; Russo, Giulia; Virgilio, Antonella; Galeone, Aldo (Biochimica et biophysica acta. General subjects, 2017)
The thrombin binding aptamer (TBA) is endowed with antiproliferative properties but its potential development is counteracted by the concomitant anticoagulant activity. Five oligonucleotides (ODNs) based on TBA sequence (GGTTGGTGTGGTTGG) and containing l-residues or both l-residues and inversion of polarity sites have been investigated by NMR and CD techniques for their ability to form G-quadruplex structures. Furthermore, their anticoagulant (PT assay) and antiproliferative properties (MTT assay), and their resistance in fetal bovine serum have been tested. CD and NMR data suggest that the investigated ODNs are able to form right- and left-handed G-quadruplex structures. All ODNs do not retain the anticoagulant activity characteristic of TBA but are endowed with a significant antiproliferative activity against two cancerous cell lines. Their resistance in biological environment after six days is variable, depending on the ODN. A comparison between results and literature data suggests that the antiproliferative activity of the TBA analogues investigated could depends on two factors: a) biological pathways and targets different from those already identified or proposed for other antiproliferative G-quadruplex aptamers, and b) the contribution of the guanine-based degradation products. Modified TBA analogues containing l-residues and inversion of polarity sites lose the anticoagulant activity but gain antiproliferative properties against two cancer cell lines. This article is part of a Special Issue entitled “G-quadruplex” Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio. [Display omitted] •TBA based ODNs with l-residues and inversions of polarity sites form G-quadruplexes.•The TBA analogues do not retain the original anticoagulant activity.•The TBA analogues have a significant antiproliferative activity on cancerous cells.